Mechanisms of Vasorelaxation Induced by Hexahydrocurcuminin Isolated Rat Thoracic Aorta - Aida Moohammadaree (2018)
Copyright © 2015 John Wiley & Sons, Ltd. This study was designed to examine the vasorelaxant effects of hexahydrocurcumin (HHC), one of the major natural metabolites of curcumin from Curcuma longa, on rat isolated aortic rings, and the underlying mechanisms. Isometric tension of the aortic rings was recorded using organ bath system. HHC (1 nM to 1 mM) relaxed the endothelium-intact aortic rings pre-contracted with PE and KCl in a concentration-dependent manner. Removal of the endothelium did not alter the effect of HHC-induced relaxation. In Ca2+-free Krebs solution, HHC significantly inhibited the CaCl2-induced contraction in high K+depolarized rings and suppressed the transient contraction induced by PE and caffeine in a concentration-dependent manner. HHC was also observed to relax phobal-12-myristate-13-acetate (PMA), an activator of protein kinase C (PKC), precontracted aortic rings in a concentration-dependent manner with EC50values equivalent to 93.36 ± 1.03 μM. In addition, pre-incubation with propranolol (a β-adrenergic receptor blocker) significantly attenuated the HHC-induced vasorelaxation. These results suggest that the vasorelaxant effect of HHC is mediated by the endothelium-independent pathway, probably because of the inhibition of extracellular Ca2+influx through voltage-operated Ca2+channels and receptor-operated Ca2+channels, the inhibition of Ca2+mobilization from intracellular stores, as well as inhibition of PKC-mediated Ca2+-independent contraction. Moreover, HHC produces vasorelaxant effects probably by stimulating the β-adrenergic receptor.